2022
DOI: 10.3390/foods11101508
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Related Metabolites Affecting Taste Values in Rice under Different Nitrogen Fertilizer Amounts and Planting Densities

Abstract: The aim of this study was to explore the differences in metabolites related to rice quality formation under different nitrogen (N) fertilizers and planting densities. In this study, Yangnongxiang 28 was used as the experimental material with the following conditions: high nitrogen and low density (HNLD; high nitrogen: 360 kg·hm−2, low density: the row spacing of rice plants was 16 cm × 30 cm), medium nitrogen and medium density (MNMD; medium nitrogen: 270 kg·hm−2, medium density: the row spacing of rice plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…TY871 and TY398 ( Figure 6 H) were rated as national standard high-quality rice grade two. Previous studies have shown that grain metabolites may be one of the central factors affecting the nutritional quality and eating quality of rice [ 17 , 18 , 19 ]. In this study, NEG_M341T662 metabolites were found to be highly correlated with rice quality ( Figure S6 ), and NEG_M341T662 was highly connected to the core genes Os06g0254300 and Os03g0168100 ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TY871 and TY398 ( Figure 6 H) were rated as national standard high-quality rice grade two. Previous studies have shown that grain metabolites may be one of the central factors affecting the nutritional quality and eating quality of rice [ 17 , 18 , 19 ]. In this study, NEG_M341T662 metabolites were found to be highly correlated with rice quality ( Figure S6 ), and NEG_M341T662 was highly connected to the core genes Os06g0254300 and Os03g0168100 ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites in rice can broadly reflect the overall metabolic state of rice seeds [ 18 ]. Metabolites in grains are the substances produced by rice that are most directly related to the ability to adapt to the environment and have a critical impact on rice quality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites in rice grains might be used to assess the types and compositions of metabolites with significant effects on rice quality and to completely represent the entire metabolic state of rice seeds [ 13 , 14 , 15 ]. Using metabolomic techniques, we explored changes in the quantity, species and abundance of metabolites as a function of nitrogen fertilization and planting concentration and their ultimate effects on rice quality [ 16 ]. The differences in the processing quality, AC, and taste value (TV) under altered nitrogen fertilizer and planting density treatments and their connection with metabolites were analyzed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using metabolomic techniques, we explored changes in the quantity, species and abundance of metabolites as a function of nitrogen fertilization and planting concentration and their ultimate effects on rice quality [ 16 ]. The differences in the processing quality, AC, and taste value (TV) under altered nitrogen fertilizer and planting density treatments and their connection with metabolites were analyzed [ 16 ]. Among them, lipid metabolites are a significant component influencing the TV of rice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation